Too much of a good thing? Using tax incentives to stimulate dual-earner couples - Henk-Wim de Boer; Egbert Jongen; Patrick Koot (Journal of Population Economics, 2025)
Following major tax-benefit reforms over the past decades, the Netherlands is an international front-runner in stimulating dual-earner couples via the tax system. We consider whether or not these tax incentives have perhaps gone too far. Using the inverse optimal tax method, our results indicate that the reforms resulted in social welfare weights that are no longer monotonically declining in household income, which is hard to rationalize with social welfare weights based solely on household income. However, this could be rationalized by other factors like preference heterogeneity between households or "affirmative feminist" social preferences. More challenging is our finding that the social welfare weights have become negative for single-earner couples with children 0–3 years of age, which suggests that the system is no longer Pareto optimal.
Keywords: C63; H21; H31; 330; Optimal taxation; Revealed social preferences; Couples